Potential therapeutic interventions for chronic kidney disease‐associated sarcopenia via indoxyl sulfate‐induced mitochondrial dysfunction. Issue 5 (12th June 2017) - Enoki, Yuki; Watanabe, Hiroshi; Arake, Riho; Fujimura, Rui; Ishiodori, Kana; Imafuku, Tadashi; Nishida, Kento; Sugimoto, Ryusei; Nagao, Saori; Miyamura, Shigeyuki; Ishima, Yu; Tanaka, Motoko; et al.
Abstract: Background: Chronic kidney disease (CKD) patients experience skeletal muscle wasting and decreased exercise endurance. Our previous study demonstrated that indoxyl sulfate (IS), a uremic toxin, accelerates skeletal muscle atrophy. The purpose of this study was to examine the issue of whether IS causes mitochondria dysfunction and IS‐targeted intervention using AST‐120, which inhibits IS accumulation, or mitochondria‐targeted intervention using L‐carnitine or teneligliptin, a dipeptidyl peptidase‐4 inhibitor which retains mitochondria function and alleviates skeletal muscle atrophy and muscle endurance in chronic kidney disease mice. Methods: The in vitro effect of IS on mitochondrial status was evaluated using mouse myofibroblast cells (C2C12 cell). The mice were divided into sham or 5/6‐nephrectomized (CKD) mice group. Chronic kidney disease mice were also randomly assigned to non‐treatment group and AST‐120, L‐carnitine, or teneligliptin treatment groups. Results: In C2C12 cells, IS induced mitochondrial dysfunction by decreasing the expression of PGC‐1α and inducing autophagy in addition to decreasing mitochondrial membrane potential. Co‐incubation with an anti‐oxidant, ascorbic acid, L‐carnitine, or teneligliptine restored the values to their original state. In CKD mice, the body and skeletal muscle weights were decreased compared with sham mice. Compared with sham mice, the expression of interleukin‐6 and atrophy‐related factors such as myostatin and atrogin‐1 was increased in the skeletal muscle of CKD mice, whereas muscular Akt phosphorylation was decreased. In addition, a reduced exercise capacity was observed for the CKD mice, which was accompanied by a decreased expression of muscular PCG‐1α and increased muscular autophagy, as reflected by decreased mitochondria‐rich type I fibres. An AST‐120 treatment significantly restored these changes including skeletal muscle weight observed in CKD mice to the sham levels accompanied by a reduction in IS levels. An L‐carnitine or teneligliptin treatment also restored them to the sham levels without changing IS level. Conclusions: Our results indicate that IS induces mitochondrial dysfunction in skeletal muscle cells and provides a potential therapeutic strategy such as IS‐targeted and mitochondria‐targeted interventions for treating CKD‐induced muscle atrophy and decreased exercise endurance.